Anisotropic topographies restore endothelial monolayer integrity and promote the proliferation of senescent endothelial cells - Exarchos, Vasileios; Neuber, Sebastian; Meyborg, Heike; Giampietro, Costanza; Chala, Nafsika; Moimas, Silvia; Hinkov, Hristian; Kaufmann, Friedrich; Pramotton, Francesca M.; Krüger, Katrin; Rodriguez Cetina Biefer, Hector; Cesarovic, Nikola; et al. (Frontiers in Cardiovascular Medicine, 2022)
Thrombogenicity remains a major issue in cardiovascular implants (CVIs). Complete surficial coverage of CVIs by a monolayer of endothelial cells (ECs) prior to implantation represents a promising strategy but is hampered by the overall logistical complexity and the high number of cells required. Consequently, extensive cell expansion is necessary, which may eventually lead to replicative senescence. Considering that micro-structured surfaces with anisotropic topography may promote endothelialization, we investigated the impact of gratings on the biomechanical properties and the replicative capacity of senescent ECs. After cultivation on gridded surfaces, the cells showed significant improvements in terms of adherens junction integrity, cell elongation, and orientation of the actin filaments, as well as enhanced yes-associated protein nuclear translocation and cell proliferation. Our data therefore suggest that micro-structured surfaces with anisotropic topographies may improve long-term endothelialization of CVIs.